2004
DOI: 10.1002/ar.a.20053
|View full text |Cite
|
Sign up to set email alerts
|

Subectodermal microfibrillar bundles are organized into a distinct parallel array in the developing chick limb bud

Abstract: In this study, a unique fiber system in the subectodermal mesenchyme of the chick limb bud was visualized immunohistochemically with the use of a novel monoclonal antibody termed "FB1." This antibody stained a subset of extracellular fibers in the embryonic mesenchyme. Among the fibers visualized, those running perpendicularly to the limb bud ectoderm became progressively prominent in their thickness and length, and organized into a parallel array in the subectodermal region. This fiber system was distinct fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 61 publications
3
17
0
Order By: Relevance
“…Hurle et al (1988Hurle et al ( , 1989 reported unique argyrophilic fibrils oriented dorsoventrally in the digital and toe plates of the developing limb bud. We have further characterized those fibrils ultrastructurally and immunohistochemically and showed that the fibrils consisted of tubular-appearing microfibrils immunoreactive for fibrillin (Isokawa et al, 2004). It was also suggested in the latter report that MFs with similar immunohistochemical characteristics emerge differentially in the presumptive dermis of the avian embryo, probably depending on local mechanophysiological demands.…”
supporting
confidence: 54%
See 4 more Smart Citations
“…Hurle et al (1988Hurle et al ( , 1989 reported unique argyrophilic fibrils oriented dorsoventrally in the digital and toe plates of the developing limb bud. We have further characterized those fibrils ultrastructurally and immunohistochemically and showed that the fibrils consisted of tubular-appearing microfibrils immunoreactive for fibrillin (Isokawa et al, 2004). It was also suggested in the latter report that MFs with similar immunohistochemical characteristics emerge differentially in the presumptive dermis of the avian embryo, probably depending on local mechanophysiological demands.…”
supporting
confidence: 54%
“…Immunoreactivity for fibrillin is known to be positive in the limb bud in its initial budding phase (Isokawa et al, 2004). Subectodermal fibrils immunoreactive for fibrillin became aligned perpendicularly to the covering ectoderm and organized into a characteristic array of vertical MFs by ED4 ( Fig.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations